Elektrochemická analýza resveratrolu ve víně - Hladíková, Jaroslava; Komínková, Markéta; Ruttkay-Nedecký, Branislav; Kopel, Pavel; Trnková, Libuše; Zítka, Ondřej; Adam, Vojtěch; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
Previously, it has been proved that resveratrol exhibits beneficial effect towards human health, maily due to its antioxidant attributes. Naturally, resveratrol occurs in its trans- form and is contained in plenty of plants, but the highest levels were determined in grapevine (Vitis vinifera L.). Thus, a wine contains negligible amounts of this attractive substance and consumption of a wine in appropriate quantity provides advantageous effects on the human body.
Keywords: Stilbenes; víno; stilbeny; Fruit; Vitis; Polyphenols; Wine; polyfenoly; ovoce